Cerebral amyloidoma is characterized by B‐cell clonality and a stable clinical course. (13th March 2017) - Heß, Katharina; Purrucker, Jan; Hegenbart, Ute; Brokinkel, Benjamin; Berndt, Rouven; Keyvani, Kathy; Monoranu, Camelia M.; Löhr, Mario; Reifenberger, Guido; Munoz‐Bendix, Christopher; Kalla, Jörg; Groß, Justus; et al.
Abstract: Amyloidomas are rare amyloid‐containing lesions, which may also occur in the central nervous system. Etiology, pathogenesis and clinical course are poorly understood. To gain more insight into the biology of cerebral amyloidoma, they aimed to characterize its histopathological, molecular and clinical features in a retrospective series of seven patients. FFPE tissue specimens were examined using immunohistochemistry, chromogenic in situ hybridization (CISH) for light chains kappa and lambda as well as an IgH gene clonality analysis. Follow‐up information was gathered by reviewing patient records and imaging results. Median age of the three males and four females was 50 years (range: 35–53 years). All cerebral amyloidomas were located supratentorially and were classified as lambda light chain amyloidosis (AL‐λ; n = 6) and kappa light chain amyloidosis (AL‐κ; n = 1) on immunohistochemistry and CISH. B‐cell clonality was confirmed by IgH gene clonality assay in all cases examined. After a median follow‐up of 21 months, all patients were alive and showed stable disease. No progression to systemic disease was observed. In conclusion, their data suggest that cerebral amyloidoma is a local disease characterized by B‐cell clonality and associated with a stable clinical course.